The Effect of Some Pesticides on the Cryptolaemus montrouzieri Mulsant (Coleoptera: Coccinellidae) the Predator of citrus mealy bug Planococcus citri (Risso) (Coccoidea, Pseudococcidae, Hemiptera) - El–Awami, Ifdial. Omar. (Al-Mukhtar Journal of Sciences, 2000)
A new version of insect control has been implemented in the last decade or so, after the hazardous effect of various pesticides on both the beneficial arthropods and the environment was observed. The integrated control started to gain acceptability by agriculture workers for its great advantages. The goal of this study to contribute more information about insecticides selectivity on Cryptolaenius tnontrouzieri the natural predator of the citrus mealy bug Panococcus citri so that some of these chemicals might be implemented in integrated control program. The results of the duration of the harmful activity indicated that, Methidthion were short–lived insecticide, less than 3 days and Methomyl, Propoxture and Permethrin was slightly persistent less than 13 days. Therefore; Cryptolaemus nontrouzieri could be released safely in the field without the risk of side–effects two weeks after treatment with these compounds. Few of these compounds namely, Benzoximate, Pirimiphose–methyl, Lindane and Sulphur inspite of less toxic than previous compounds did have long term effect on fecundity.